Developing Digital Entrepreneurship Learning Model: 4-D Competencies-Based for Millennial Generation in Higher Education - Erdisna, Erdisna; Ridwan, Muhammad; Syahputra, Hadi (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
This present R&D study aims to develop a digital model of millennial entrepreneurship in universities attached to the Information System Design Analysis course with 4C competencies (Communication, Collaboration, Critical thinking, and Creativity). The problem is that students only make software to fulfill course assignments without thinking about the usefulness of the software they produce as a means of digital entrepreneurship. The research method used was a 4-D development model consisting of 4 stages: Definition, Design, Development, and Dissemination. The literacy model testing carried out showed that the average score was 0.840, which stated that the model was distributed as valid and doable to use. The average results of the practicality assessment of the operation of the Digital entrepreneurship literacy model grounded on the perception of the experimental class scholars were 87 in the practical order. The results show that the digital entrepreneurship model encourages students to open businesses using information technology. The development of this entrepreneurship digital learning model can train students to have an entrepreneurial spirit. In addition, it can improve students' skills in 21st-century literacy.